Medicinal Properties of Plantago Major L. Plant and Agrotechnology of Growing - Baxieva L.A; Erjanova Sh (Zien Journals, 2024)
The researches were carried out at the experimental field of the "Shurtanboy" MFY grain and rice scientific production association, Nukus district of the Republic of Karakalpakstan. In this regard, experiments were carried out on different sowing methods and encapsulation of seeds of spring soft wheat resistant to drought and diseases, with high yield and high grain quality, in weak and medium salinity areas of the Republic of Karakalpakstan, especially in the island region
Keywords: soft wheat; No-till technology; seed encapsulation